2021
DOI: 10.3390/ijerph181910402
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Use, Systemic Inflammation, and Depression

Abstract: Background: E-cigarette use (vaping) is an emerging public health problem. Depression has been found to be associated with e-cigarette use, and vaping and depression are each associated with elevated systemic inflammation. To date, the role of inflammation in the relationship between vaping and depression has not been explored. Objective: To assess the independent associations between e-cigarette use, depression, and inflammation, and to investigate whether the likelihood of depression among current e-cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Similar to the literature on the general population ( Farrell et al, 2021 , Obisesan et al, 2019 , Park et al, 2017 , Saeed et al, 2020 , Sung, 2021 ), we found significant associations between e-cigarette use and anxiety/depression symptoms among Black/African American adults. While anxiety/depression symptoms were not associated with former e-cigarette use in this population, they were associated with current daily or someday e-cigarette use.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to the literature on the general population ( Farrell et al, 2021 , Obisesan et al, 2019 , Park et al, 2017 , Saeed et al, 2020 , Sung, 2021 ), we found significant associations between e-cigarette use and anxiety/depression symptoms among Black/African American adults. While anxiety/depression symptoms were not associated with former e-cigarette use in this population, they were associated with current daily or someday e-cigarette use.…”
Section: Discussionsupporting
confidence: 87%
“…Studies revealed that individuals who perceived e-cigarettes as less harmful than cigarettes were more likely to be ever or current users of e-cigarettes ( Brose et al, 2015 , Cooper et al, 2016 , Huang et al, 2019 , Malt et al, 2020 , Rass et al, 2015 , Wackowski and Delnevo, 2016 ). Those with anxiety/depression symptoms were more likely to use e-cigarettes than their counterparts without anxiety/depression ( Farrell et al, 2021 , Obisesan et al, 2019 , Park et al, 2017 , Saeed et al, 2020 , Sung, 2021 ). Individuals with mental health disorder symptoms perceived e-cigarette use as less harmful, but they were more likely to use e-cigarettes than those who did not use e-cigarettes ( Baltz and Lach, 2019 , Hefner et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 20 million adults in the United States suffer from depression (30), and multiple studies have demonstrated comorbidity between depression and electronic cigarette use (16,(31)(32)(33)(34)(35)(36)(37)(38)(39). This association is also dose-dependent, where greater amounts of nicotine consumed were associated with greater self-reported depressive symptoms (40).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…As nicotine has psychoactive properties 21 , it is possible that adolescents with depressive symptoms use electronic cigarette as a method to intake nicotine, similar to the pattern in conventional cigarette use, or vice versa 22 . Previous studies and reviews 13,[22][23][24][25] have reported that depression was associated with electronic cigarette use. However, as depression occurs in a gradient rather than as a binary, the pattern of associations between levels of depression and electronic cigarette use has not been fully explored.…”
Section: Introductionmentioning
confidence: 96%